Bleeding Diathesis Secondary to a Heparin-Like Anticoagulant in a Patient with Multiple Myeloma—A Case Report and Review of Literature - Nihar Desai; Seema Biswas; Dinesh Chandra; Ruchi Gupta; Anshul Gupta; Rajesh Kashyap (Indian Journal of Medical and Paediatric Oncology)
Multiple myeloma (MM) is a clonal plasma cell disorder that commonly presents with anemia, renal failure, hypercalcemia, and lytic bone lesions. MM is also frequently associated with thrombotic complications; however, it may rarely present with bleeding diathesis. We report a case of a 42-year-old gentleman with relapsed immunoglobulin G lambda MM who presented with epistaxis, gingival bleeding, and oozing at the venepuncture site. Routine tests of coagulation revealed a prolonged prothrombin time (PT), activated partial thromboplastin time (aPTT), and thrombin time. The PT and aPTT failed to correct with pooled normal plasma and the patient was thus diagnosed to have an acquired heparin-like anticoagulant (HLAC). The source of this HLAC has long been debated, but recent data have demonstrated that this HLAC may be the paraproteins produced by the malignant plasma cells. The patient was treated with intravenous protamine sulfate, repeated cycles of plasma exchange, and a daratumumab-based quadruplet regimen but eventually succumbed to an intracranial hemorrhage. HLAC is a rare but potentially fatal complication of MM that must be considered when patients with MM present with bleeding diathesis.